Identification of Genes Related to Nitrogen Uptake in Wine Strains of Saccharomyces Cerevisiae - Contreras-Opazo, A; Martinez-Fernandez, C; Ganga-Munoz, M; Garcia-Mena, V; Salinas-Sanhueza, F (2012)
Sin Editorial Disponible